Effect of Rape Seeds’ Pre-sowing Treatment with Complex Cryoprotectant-Based Agrochemical Preparations on Plant Winter Hardiness and Yielding Capacity - Dyakonenko, G. Yu.; Lysak, Yu. S.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of pre-sowing treatment of winter rape seeds with PEO-1500 cryoprotectant, Jupiter and Dorsay preparations on their frost and winter hardiness and yielding capacity has been studied. It was found that seed treatment with these preparations increased the seed capacity to germinate under lowered temperature (5–10°C), and also plant frost hardiness and content of soluble carbohydrates. A correlation between winter hardiness level of winter rape and content of soluble carbohydrates has been established.